Clima ético em organizações públicas: o mapa de um hospital universitário - Carvalho, Wagner de (2014)
The process of introducing ethics as a management tool must occur in four phases: identification, development, implementation, and evaluation. Identify the ethical climate knowing the culture of an organization are extremely important to the achievement of desired outcomes aspects. The climate in HUCAM may be considered good. The health care team at the hospital are represented by 45 % of experts. Technical qualification of servers provides a good foundation for the professional dealing with patients, establish a good relationship, and offer a good service. The large number of observed conflicts, however, points to the need for development of affective attributes of the area. The main value pursued by professionals HUCAM is respect. There is a predominance of ethical principles in the hospital environment. The overvaluation of punctuality and attendance brings as a consequence the overhead of activities for some servers. Most employees do not feel well informed about the future plans of the hospital. Several factors may influence the ethical climate of an organization such as unmotivated staff, lack of synergy between the various sectors of work, difficult relationships between managers and co-workers, lack of goals, lack of collegiality and teamwork, poor communication, failure to conduct the interfaces of work processes; personal conflicts; gratified system functions, and the degree of satisfaction of servers, among others. Models of managerial and participatory management, however, require to see you succeed, a high degree of commitment of its employees to companies. It is very important pay attention to the human assets of the organization, which has been gaining attention since they depend on this heritage, success and achievement of the objectives of the firm. Therefore, it is necessary to maintain the organization, not only competent employees, but competent and motivated employees. In this context we have the organizational climate as a facilitator of commitment and involvement of all members with the interests of the organizatio